Examining the Factors that Influence Firm Performance In Ghana: A GMM And OLS Approach: Array - Dodoo, Regina; Tetteh Donkor, Daniel; Appiah, Michael (The Journal of Accounting and Management, 2021)
This research aims to establish the determinants of firm performance in 15 non-financial Ghanaian companies listed on the Ghana Stock Exchange, over a period of 10 years (2008-2017). The analysis is based on two methods of estimation; two-step system generalized method of moments (GMM) and ordinary least square (OLS) method. The new empirical evidence derived from the results of the analysis reveals that firm size (SIZE), growth (GR) and cash flow ratio (CFR), significantly and positively determines firm’s performance whereas debt to equity (DE) exerted negative influence on firm performance. Robustness test conducted using the three-stage least-squares regression, indicates similar results with the main findings of the study. These results implies that, firms that rely on debt to execute its operations run at a higher risk of insolvency.